2005
DOI: 10.1111/j.1440-1797.2005.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and urinary N‐acetyl‐β‐ d‐glucosaminidase activity in paediatric patients with idiopathic hypercalciuria

Abstract: Tubular impairment is highly probable in children with IH, but there is a poor relationship with the degree of calcium leakage. Idiopathic hypercalciuria should be considered as a risk factor for stunted growth and low bone mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
13
1
2
Order By: Relevance
“…1). Skalova et al [13] reported a negative correlation between 24-h urine Ca and spinal BMD. In our patients, we found a strong and almost significant inverse correlation between urine Ca and BMD of the femoral neck, but no such trend was appreciated between urine Ca and spinal BMD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1). Skalova et al [13] reported a negative correlation between 24-h urine Ca and spinal BMD. In our patients, we found a strong and almost significant inverse correlation between urine Ca and BMD of the femoral neck, but no such trend was appreciated between urine Ca and spinal BMD.…”
Section: Discussionmentioning
confidence: 98%
“…The association of hypercalciuria or hypercalciuric stone disease with osteopenia in children was confirmed by Freundlich et al [10], Penido et al [11], and Schwaderer et al [12], who reported, respectively, that 38%, 37%, and 47% of hypercalciuric children studied had reduced BMD. Skalova et al [13] found an inverse correlation between urine Ca and BMD in children with IH. Reduced BMD in children and adolescents is a risk factor for diminished peak bone mass, for life-long low BMD, and eventual bone fractures [14].…”
Section: Introductionmentioning
confidence: 97%
“…However, it is generally considered that IH is caused by an alteration in calcium homeostasis at sites where large amounts of calcium must be precisely controlled [5]. Several studies have shown decreased bone mineral density (BMD) in patients with IH [6][7][8][9][10][11][12][13][14][15][16][17][18]. This progressive decrease in bone mineral content suggests that osteoclasts and osteoblasts might play a key role in the chain of events leading to hypercalciuria.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced bone mineral density (BMD) is a commonly reported condition in pediatric patients diagnosed with idiopathic hypercalciuria (IH) [1][2][3][4][5][6][7], but the precise mechanisms of bone loss or failure of adequate bone mass gain remain as yet unknown. There have been relatively few studies on bone mass in pediatric IH.…”
Section: Introductionmentioning
confidence: 99%
“…There have been relatively few studies on bone mass in pediatric IH. When performed, BMD measurements have consistently disclosed decreased z-scores at the lumbar spine and, to a lesser extent, at the femoral neck [1][2][3][4][5][6][7]. The largest accumulation of bone mass occurs during childhood and adolescence, reaching peak bone mass at the end of the second decade of life [8][9][10].…”
Section: Introductionmentioning
confidence: 99%